Auditors' experience in financial statement fraud detection: the role of professional scepticism and idealism / Syamsuri Rahim ... [et al.] - Rahim, Syamsuri; Ahmad, Hamzah; Widya, Andi; -, Nur Wahyuni; Junaidi, Junaidi (Accounting Research Institute (ARI), Universiti Teknologi MARA, Shah Alam, 2023)
The number of financial misstatements globally and their correlation to auditors' roles in detecting fraud has raised questions about professionalism among auditors. Various studies have investigated how to reduce cooking books among companies. This study aimed to examine the role of auditors' experience and how to detect fraud in financial statements through auditors' professional scepticism and idealism. The sample consisted of 446 auditors and structural equation modelling (SEM) was applied to examine the research hypotheses. This study found that auditors' experience positively affected professional scepticism and had a less significant impact on auditors' idealism. Furthermore, mediator variables, namely, auditors' professional scepticism and idealism, had a positive influence on fraud detection and fully mediated the relationship between auditors' experience and skill to detect fraud in financial statements. This research can contribute to providing recommendations to auditors to detect fraud in financial statements because auditors' attitudes, behaviours, skills, and education can help detect fraud in financial statements. The limitations of this research lie in the research method, the time of the research, and the limited number of respondents who participated in the study.